A Systematic Review of the Protective Actions of Cat’s Whiskers (Misai Kucing) on the Central Nervous System - Chung, Yin-Sir; Choo, Brandon Kar Meng; Ahmed, Pervaiz Khalid; Othman, Iekhsan; Shaikh, Mohd. Farooq (Frontiers in Pharmacology, 2020)
Orthosiphon stamineus (OS) or Orthosiphon aristatus var. aristatus (OAA) is commonly known as cat’s whiskers or “misai kucing”. It is an herbaceous shrub that is popular in many different traditional and complementary medicinal systems. Its popularity has been justified by the plethora of studies that have shown that the secondary metabolites of the plant has effects that range from anti-inflammatory and gastroprotective to anorexic and antihypertensive. As such, OS could also be a potential treatment for Central Nervous System (CNS) disorders. However, a cohesive synthesis of the protective actions of OS was lacking. This systematic review was therefore commenced to elaborate on the various protective mechanisms of OS in the CNS. The PRISMA model was used and five databases (Google Scholar, SCOPUS, SpringerLink, ScienceDirect, and PubMed) were searched with relevant keywords to finally identify four articles that met the inclusion criteria. The articles described the protective effects of OS extracts on Alzheimer’s disease, epilepsy, learning and memory, oxidative stress, and neurotoxicity. All the articles found were experimental or preclinical studies on animal models or in vitro systems. The reported activities demonstrated that OS could be a potential neuroprotective agent and might improve CNS conditions like neurodegeneration, neuroinflammation, and oxidative stress.